Investigation of the Relationship between Free Time Management, Social Media Addiction and Life Satisfaction of University Students During the COVID-19 Pandemic Process - Recep Cengiz; Batuhan Er (Journal of Educational Issues, 2024)
The aim of this study is to examine the relationship between university students free time management, social media addiction and life satisfaction during the COVID-19 pandemic. The sample group of the study consists of 114 female and 291 male university students. Free Time Management Scale, Social Media Addiction Scale and Life Satisfaction Scale were used as data collection instruments in the research. SPSS 25 package program was used in the analysis of the data; In their statistical representations, arithmetic mean, standard deviation and frequency values are presented. For analysis to the data set; T-Test for Independent Samples, Multivariate Analysis of Variance (MANOVA), One Way Analysis of Variance (ANOVA) and Pearson Correlation Test were applied. When the T-Test results for Independent Samples are examined; In terms of gender variable, a significant difference was found in favor of women in the “goal setting and method” sub-dimension of the Free Time Management Scale. When the results of Multivariate Analysis of Variance MANOVA test were examined; In terms of daily social media usage times, a significant difference was found in the sub-dimensions of preoccupation, mood regulation, repetition and conflict of the Social Media Addiction Scale. As a result, it is seen that there is a relationship between university student participants’ free time management and social media addiction. However, no relationship was found between life satisfaction and social media addiction. While a low negative correlation was found between the total score of life satisfaction and the free time management programming sub-dimension, no correlation was found between the sub-dimensions of goal determination and method, assessment and free time attitude.